Language-in-Education Policy for English Language Teaching in Public Schools of Kazakhstan: Top-Down vs. Bottom-Up Approaches - Dinara Imanova; Assel Akzhigitova; Anastassia Zabrodskaja (Education Sciences)
This research explores the Kazakhstani public schools’ English language teaching (ELT) policy. Despite numerous policy reforms to enhance English language teaching (ELT) in Kazakhstani public schools, relatively little research has examined teachers’ perspectives on the interface between the top-down policy and classroom realities. Therefore, this study addresses this gap by investigating the lived experience of English language (EL) teachers from 17 regions, highlighting significant disparities in resources, training, and personnel. The findings suggest that top-down policies create a mismatch with realities at the classroom level, where training is insufficient. Resources are lacking, and ELT policy intentions have not met the real needs of the EL teachers. This paper criticises the ELT policymaking for the marginalisation of the voices of EL teachers. Instead, it advocates a more participatory approach at the bottom of policymaking, which embodies educators themselves. This paper contributes to the wider discussion on language policy by drawing attention to the role of teacher agency, emphasising contextually valid and equitable policies that would address the relevance of ELT in multilingual and resource-lacking contexts like Kazakhstan.